Asymmetric synthesis of both enantiomers of novel tetracyclic heterocycle, furo[3',2':2,3]pyrrolo[2,1-alpha]isoquinoline derivative via a diastereoselective N-acyliminium ion cyclization - Lee, JY; Lee, YS; Chung, BY; Park, H (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
An efficient synthesis of both enantiomers of tetracyclic isoquinoline derivative (-)-2 and (+)-2 was accomplished starting from L-malic acid and L-tartaric acid, respectively. The key step is the stereoselective introduction of quaternary carbon-center in ring juncture using a diastereoselective N-acyliminium ion cyclization of chiral enamides (1, 3). (C) 1997, Elsevier Science Ltd.